2014
DOI: 10.1007/s00441-014-1817-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of dendritic-cell-like S100β-positive cells in rat anterior pituitary gland

Abstract: S100β-protein-positive cells in the anterior pituitary gland appear to possess multifunctional properties. Because of their pleiotropic features, S100β-positive cells are assumed to be of a heterogeneous or even a non-pituitary origin. The observation of various markers has allowed these cells to be classified into populations such as stem/progenitor cells, epithelial cells, astrocytes and dendritic cells. The isolation and characterization of each heterogeneous population is a prerequisite for clarifying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Next, the expression of Gpr68 and Il-6 was examined in the round-and process-types of S100β-positive cells, separated by reference to their different adherent properties to laminin, an extracellular matrix molecule. Expression of Il-6 in the round-type was confirmed as previously reported (Horiguchi et al 2014). RT-PCR showed clearly that Gpr68 was expressed in the round-type similarly to Il-6 ( Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Next, the expression of Gpr68 and Il-6 was examined in the round-and process-types of S100β-positive cells, separated by reference to their different adherent properties to laminin, an extracellular matrix molecule. Expression of Il-6 in the round-type was confirmed as previously reported (Horiguchi et al 2014). RT-PCR showed clearly that Gpr68 was expressed in the round-type similarly to Il-6 ( Fig.…”
Section: Resultssupporting
confidence: 86%
“…GFP-positive cells were plated onto 8-well glass chamber slides (1×10 5 cells/cm 2 /well; Nalge Nunc International, Rochester, N.Y., USA) that had been coated with laminin substrate (Millipore, Bedford, Mass., USA) at 10 μg/cm 2 , with 400 μl Medium 199 with Earle's salts (Life Technologies, Palo Alto, Calif., USA), supplemented with 10 % fetal bovine serum (Sigma-Aldrich, St. Louis, Mo., USA), 0.5 U/ml penicillin and 0.5 μg/ml streptomycin (Life Technologies). The GFP-positive cells were cultured for 24 h. The majority of GFP-positive cells showed flattened and markedly extended cytoplasmic processes (process-type) but a small number of GFP-positive cells retained their round shape (round-type), as described previously (Horiguchi et al 2014). The round-type cells were removed from the dish by gentle pipetting and collected by centrifuge from the retrieved medium, followed by cultivation again for 24 h in 400 μl medium on laminin-coated 8-well glass slides.…”
Section: Animalsmentioning
confidence: 99%
“…For example, in addition to S100a4-Cre activity in the gonads, S100A4 protein has been reported to be expressed in astrocytes of the brain (42). GFP expression driven by the S100β promoter in rat is also detected in bones and adipose tissues (43). However, we have demonstrated that pituitary gonadotropin deficiency in S100a4-Cre;Ptch1 fl/fl mutants is not dependent on gonadal factors ( Figure 5E); in addition, a transgenic mouse line that is depleted of adipose tissues (Bscl2 -/mice) does not exhibit a pituitary phenotype similar to that in the S100a4-Cre;Ptch1 fl/fl mutants, supporting the idea that reduced adiposity in the latter is not the primary cause of their pituitary abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…On its own, S100β marks multiple populations, displaying expression in the SOX2‐positive marginal zone region, in the morphologically distinct folliculostellate cells and reported to be expressed in pituicytes. In rat, at least two distinct S100β populations have been isolated, one with processes typical of folliculostellate cells, which is positive for GFAP and vimentin and a second, morphologically rounded cell type lacking processes, which express dendritic markers . Multiple functions have been put forward for S100β‐positive folliculostellate cells reviewed comprehensively elsewhere , including providing structural support and enabling communication within the pituitary facilitating pulsatile hormone secretion .…”
Section: Cellular and Molecular Properties Of Pscsmentioning
confidence: 99%
“…). The in vitro clonogenic potential of SOX2 cells does not differ between the two locations and it has been postulated that these cells form a network spanning the whole pituitary, making connections through their projections . Recent studies from rat have revealed that SOX2 + /S100β + double‐expressing cells include a further subset that express the gene Cxadr in vivo, which codes for coxsackievirus and adenovirus receptor (CAR), that facilitates formation of homophilic tight junctions .…”
Section: Cellular and Molecular Properties Of Pscsmentioning
confidence: 99%